PENERAPAN REHABILITASI TERHADAP PENGGUNA NARKOTIKA BERDASARKAN PASAL 54 JUNCTO PASAL 55 UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA DI KOTA PEKANBARU - Arin Rosalia; Erdianto '; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
The development of increasingly frightening narcotic crime community life, proved to be the development rate drug crimes from year to year to grow rapidly despite the existing law governing narcotics, nevertheless has many victims regardless of age and social status fell due to drug addiction. Ironically the majority of the victims are teenagers and young adults who are the nation's future. Based on this fact, there are three formulation of the problem in writing this essay, namely: First, What is the application of rehabilitation for drug users under Article 54 Juncto Article 55 of Law No. 35 of 2009 on Narcotics in Pekanbaru? Secondly, What are the constraints faced by the Government in the implementation of rehabilitation pursuant to Article 54 in conjunction with Article 55 of Law No. 35 of 2009 on Narcotics in Pekanbaru? Third, how the government's efforts to overcome obstacles in the implementation of rehabilitation pursuant to Article 54 in conjunction with Article 55 of Law No. 35 of 2009 on Narcotics in Pekanbaru?The research method in this study is a qualitative research method with empirical juridical approach or sociological law research. Data sources supported by primary and secondary data sources. Data collection techniques used were interviews, questionnaires and review of the literature. After the data collected then analyzed qualitatively, and draw conclusions with a deductive method of thinking is to analyze the problems of the general form into special shapes.From the results of research and discussion, it can be concluded that, Application Rehabilitation Of Users Narcotics under Article 54 Juncto Article 55 of Law No. 35 of 2009 on Narcotics in Pekanbaru that victims of drug users are obliged to report themselves to be rehabilitated while families and elderly victims of abuse of narcotic knowing that one of his family members to use narcotics are required to report to rehab his family, so that if Article 55 is not executed then get penalized in the form of penalties of imprisonment and fines. The constraints are the lack of implementation of rehabilitation facilities and medical personnel, the lack of community understanding of drug rehabilitation and public awareness minimya to comply with applicable law. Then made several attempts to overcome these obstacles: socializing by providing knowledge about the dangers of narcotics in the community, improve supervision of parents, and immediately report to the rehabilitation if it finds drug abuse victims.Keywords: Application - Rehabilitation - Users - Narcotics